2023
DOI: 10.4236/ojbm.2023.114102
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption of E-Services by the Informal Sector: A Case of ECIS under NAPSA

Mubanga Musenga,
Jackson Phiri

Abstract: The study was conducted to investigate the factors influencing the adoption of e-services by the informal sector under the Extension of Coverage to the Informal Sector (ECIS) under NAPSA. The study adopted the UTAUT framework model from which five variables were examined which are: performance expectancy, effort expectancy, social influence, facilitating conditions and behavioral intention to determine the factors influencing the actual use of eService systems. The researcher adopted a mixed methodology approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This implies that social influence has no effect on the adoption of digital marketing by tourism-related businesses. These results still remain the same as study by Mubanga and Phiri (2023), based on the UTAUT model, they asserted that, social influence is not significant as indicated in the table above with the Pearson correlation of 0.042. From this it can be deduced that the marketeers are not influenced by society's perception on the usage of e-NAPSA service.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This implies that social influence has no effect on the adoption of digital marketing by tourism-related businesses. These results still remain the same as study by Mubanga and Phiri (2023), based on the UTAUT model, they asserted that, social influence is not significant as indicated in the table above with the Pearson correlation of 0.042. From this it can be deduced that the marketeers are not influenced by society's perception on the usage of e-NAPSA service.…”
Section: Discussionsupporting
confidence: 76%
“…According to Mubanga and Phiri (2023), in their study to investigate the factors affecting the marketeers to adopt the E-NAPSA services the results from their findings revealed that, effort expectance is not significant as based on the Pearson correlation of −0.096. From this it can be deduced that the marketeer's effort expectant does not influence the usage of e-NAPSA services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With technological resources developing on a global scale, the mobile environment is expected to be the main infrastructure for the future of electronic payment 2 . Estimates show that as many as 50% of "smartphone"-type devices will contain interfaces that can communicate financial data without any physical contact with the payment terminal 15 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the present day, it is undeniable that the government sector significantly impacts industrial innovation. Research shows that, without governmental support, technological advancement will prompt challenges for e-commerce to grow, including law 2 . The regulation on the use of electronic signatures is reviewed and adapted to the global digital economy in some ASEAN countries 3 .…”
Section: Introductionmentioning
confidence: 99%